PENGARUH UTANG LUAR NEGERI, PENANAMAN MODAL ASING LANGSUNG DAN INVESTASI PORTOFOLIO TERHADAP NILAI TUKAR RUPIAH DI INDONESIA TAHUN 2005-2019 - Wanda, Julio; Any, Widayatsari; Darmayuda, Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research alms to determine how much influence foreign debt, foreign direct investment and portfolio investment on the rupiah exchange rate in Indonesia. This research uses independen variables of foreign debt, foreign direct investment and portfolio investment, dependent variable is rupiah exchange rate. The data used in this research is annual data from 2005-2019. The analitical method used is descriptive quantitative and analized partially or simultaneously with multiple linear regression OLS (Ordinal Least Square) processed by using E-Views 11. The result shows that, foreign debt, foreign direct investment and portfolio investment has a significant effect on the rupiah exchange rate simultaneously. Meanwhile, foreign debt has a significant positive effect on the rupiah exchange rate, foreign direct investment has a significant negative effect on the rupiah exchange rate and portfolio investment has a positive insignificant effect on the rupiah exchange rate. In addition, it was found that the value of adjusted is 81,13%.Keywords: Rupiah Exchange Rate, Foreign Debt, Foreign Direct Investment, Portfolio Investment